Associação entre alterações metabólicas, proteína c reativa ultrassensível e dilatação fluxo-mediada da artéria braquial em pacientes usuárias de anticoncepcional hormonal combinado: um estudo transversal - Sousa, Carla Roberta Macedo de (2023)
Oral combined hormonal contraceptives (CHCs) are one of the most used contraceptive methods worldwide, however, their use may have accessory effects that can generate metabolic, inflammatory, and vascular alterations. Flow-mediated dilation (FMD) measured using ultrasound is a non-invasive and low-cost method that allows assessing endothelial function and its damage.To evaluate the association of cardiovascular risk factors, Ultra-sensitive C-reactive protein (US-CRP), and brachial artery flow-mediated dilation in patients using hormonal contraceptives.This was a cross-sectional study including 109 women (18 to 40 years old) conducted between August 2017 and January 2020 who were assisted at the Brazilian Public Health System in countryside city in northeastern of Brazil.The volunteers were divided into two groups according to the use of CHCs and submitted to measurement evaluations of clinical, laboratory, and flow-mediated dilation (FMD) of the brachial artery parameters. The statistical analysis of results between groups showed the following results as total cholesterol (P = < 0.01), high-density lipoprotein, HDL (P = 0.01), triglycerides, TG (P < 0.01), and US-CRP (P = < 0.01). The FMD measurement showed changes in 5,66% (n = 03) of women who were not using CHCs and in 14,28% (n = 08) of womenusing CHCs (P = 0,148)(odds ratio, OR = 2,78, CI 95% 0,69-11,10). There were no significant changes between glycemic indexes and parameters clinicals.Users of CHCs showed higher levels of total cholesterol, HDL, and triglycerides compared to those who did not use it. The US-CRPresults showed a significant increase among CHCs users, however, no change between the FMD values was observed.